2011
DOI: 10.1055/s-0031-1295661
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Hypothermia during Neonatal Transport: Current Practices in California

Abstract: Therapeutic hypothermia initiated at <6 hours of age reduces death and disability in newborns ≥ 36 weeks' gestation with moderate to severe hypoxic ischemic encephalopathy. Given the limited therapeutic window, cooling during transport becomes a necessity. Our goal was to describe the current practice of therapeutic hypothermia during transport used in the state of California. All level III neonatal intensive care units (NICUs) were contacted to identify those units providing therapeutic hypothermia. An electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 16 publications
1
11
0
1
Order By: Relevance
“…A survey of cooling centers in California in 2010 showed that 64% performed cooling in transport. 22 The same authors found that only 44% of infants cooled in transport achieved a target temperature (33 C-34 C) at the time of admission to the cooling center. 16 Fairchild et al used passive cooling at referral and active cooling by transport team.…”
Section: Discussionmentioning
confidence: 96%
“…A survey of cooling centers in California in 2010 showed that 64% performed cooling in transport. 22 The same authors found that only 44% of infants cooled in transport achieved a target temperature (33 C-34 C) at the time of admission to the cooling center. 16 Fairchild et al used passive cooling at referral and active cooling by transport team.…”
Section: Discussionmentioning
confidence: 96%
“…In one study, as many as one third of infants arrived in NICU with a core temperature of <33°C [23]. Deep hypothermia may induce bradycardia and arrhythmia [20], thrombocytopaenia [6] requiring platelet transfusion [21] although overall haemostasis may not be affected [22]. …”
Section: Discussionmentioning
confidence: 99%
“…Infant Cooling Evaluation Collaboration (ICE study) clinical trial has reported that whole body cooling using low tech methods was safe and effective for HIE cases. Owing to its practicality and low cost, it is used by several centers even in high resource countries [14,22,23] . Still, one should be aware of the highest variation of temperature with this cooling method [14] .…”
Section: Discussionmentioning
confidence: 99%
“…Ongoing studies on this issue by NICDH reported a term late hypothermia that could be expected to provide insights as to whether the later timely application of therapeutic hypothermia is beneficial [9] . Cooling during transport could be an alternative approach as initiation of effective hypothermia is achieved significantly earlier, but clinical protocols and devices for cooling in transport are essential to ensure safety and efficacy [23,25] .…”
Section: Discussionmentioning
confidence: 99%